Characterization of transcriptomes from sexual and asexual lineages of a New Zealand snail (Potamopyrgus antipodarum). (27th December 2012) - Wilton, Peter R.; Sloan, Daniel B.; Logsdon Jr, John M.; Doddapaneni, Harshavardhan; Neiman, Maurine
Abstract: Understanding the evolution and maintenance of sexual reproduction is one of the central challenges of evolutionary biology, yet we know very little about how sex influences molecular evolution. The New Zealand freshwater snail Potamopyrgus antipodarum is ideally suited to address this knowledge gap because obligately sexual individuals often coexist with multiple independently derived obligately asexual lineages. This unusual situation allows direct comparisons both between sexual and asexual P. antipodarum and across populations that differ in the relative frequency of sexual individuals. As such, P. antipodarum has received a great deal of attention as a model system for the maintenance of sex in nature and is also used as a model for environmental toxicology and biological invasions. Molecular genetic resources for P. antipodarum will thus be useful to investigators in a variety of biological fields. We used 454 sequencing of cDNA libraries to generate transcriptomes from two sexual and two asexual P. antipodarum lineages. A de novo assembly of 116.7 Mb of sequence reads produced 41 396 contigs, and sequence similarity‐based Gene Ontology annotations were obtained for 3740 contigs. We detected 408 315 SNP loci and 7315 microsatellite loci, which together represent the first genome‐scale resource available for P . antipodarum . Raw 454 read sequences, contig sequences, annotation data and polymorphism data are publicly available in a searchable online database and for download at http://www.biology.uiowa.edu/neiman/transcriptome.php .